HAS-BLED score as a predictor of bleeding complications from catheter ablation of atrial fibrillation: A subanalysis of the Japanese Anti-Coagulation Regimen Exploration in AF Catheter Ablation Registries. Issue 1 (January 2020) - Inoue, Koichi; Hirao, Kenzo; Aonuma, Kazutaka; Kumagai, Koichiro; Kimura, Masaomi; Miyauchi, Yasushi; Tsushima, Eiki; Okumura, Ken; ,
Highlights: Bleeding complication risk of atrial fibrillation ablation was assessed. The mHAS-BLED score was more useful than the ATRIA and ORBIT scores. High-risk patients were best identified by the mHAS-BLED score of ≥3. Less risk of bleeding complications in rivaroxaban cohort than warfarin. Abstract: Background: The ATRIA, Outcomes Registry for Better Informed Treatment (ORBIT), and modified (m) HAS-BLED (excluding a labile international normalized ratio element from the HAS-BLED score) scores are currently used to predict the bleeding risk in atrial fibrillation (AF) patients receiving oral anticoagulant treatment. We assessed the usefulness of these scores in estimating the catheter ablation (CA)-related bleeding risk in AF patients from the Japanese Anti-Coagulation Regimen Exploration in AF Catheter Ablation Registry (JACRE). Methods: We investigated 1322 consecutive patients enrolled in the prospective, multicenter JACRE registry of AF patients receiving CA. The patients also received rivaroxaban ( n  = 1118) or warfarin ( n  = 204) during the perioperative period and complications were monitored for 30 days post-surgery. Results: Periprocedural bleeding complications occurred in 42 patients (3.2%) and were significantly associated with the mHAS-BLED [hazard ratio = 1.46, 95% confidence interval (1.06–2.01)], ATRIA [1.16 (1.00–1.35)], and ORBIT [1.29 (1.06–1.57)] scores. However, only the mHAS-BLED score predicted a significantly greater bleeding prevalence in the high-score group than in the low-score group stratified by a threshold maximizing the sensitivity and specificity (threshold = 3, p  < 0.001). The incidence of all bleeding complications was significantly lower in the rivaroxaban cohort in patients with a mHAS-BLED score ≥3 (rivaroxaban vs. warfarin cohort, 5.56% vs. 25%, p  = 0.028). Conclusions: All three common bleeding scores were associated with a periprocedural risk of CA-related bleeding in AF patients and a mHAS-BLED score ≥3 best distinguished high-risk patients from low-risk patients.